Pengaruh Model Pembelajaran ARIAS (Assurance, Relevance, Interest, Assessment, Saticfaction) Terhadap Hasil Belajar PAK Siswa Kelas IX SMP N 3 Lintong Nihuta Kabupaten Humbang Hasundutan Tahun Pembelajaran 2023/2024 - Chyristina Sianturi; Malani Simanungkalit; Dame Taruli Simamora (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2023)
The purpose of this research is to determine whether there is an influence of the ARIAS Learning Model on the PAK Learning Outcomes of Class IX Students at SMP N 3 Lintongnihuta. The method used in this research is a quantitative method with a Pre-Experiment Design research type, one group pre-test and post-test design. The population is all class IX of SMP Negeri 3 Lintong Nihuta for the 2023/2024 academic year, totaling 191 people and a sample of 32 people was determined using the purposive sampling technique. Data was collected with a test item of 20 questions. The results of data analysis show that there is an influence of the ARIAS Learning Model (Assurance, Relevance, Interest, Assessment, Satisfaction) on the PAK Learning Outcomes of class IX students of SMP N 3 Lintongnihuta Humbang Hasundutan Regency for the 2023/2024 Academic Year as proven by the t test where it is obtained that tcount > ttable ( α=0.05; dk=n-2=30) which is 11.720 > 2.042. Thus, H0 is rejected and Ha is accepted, namely that there is an influence of the ARIAS Learning Model (Assurance, Relevance, Interest, Assessment, Satisfaction) on the PAK Learning Outcomes of class IX students at SMP N 3 Lintongnihuta, Humbang Hasundutan Regency for the 2023/2024 academic year.